Analisis Pemikiran Hukum Islam Terhadap Pernikahan Khuntsa Musykil - Ibadurrohman, Ibadurrohman; Nurjanah, Happy; Ulfa , Hidayatun (El-Qenon: Journal of Islamic Law, 2024)
Khuntsa in the perspective of islam is grouped into two kinds. The first is the khuntsa which is contemporarily known as khuntsa ghair musykil, whose genital can be distinguished as male or female. While the second one is a khuntsa musykil who has double genitals that cannot be distinguished as male or female. As a human being, khuntsa has biological needs to be fulfilled. Islam gives the syariat of marriage as a place to fulfill the biological desire. However the problemis how the assurance of the marriage law for the khuntsa. How is the perspective of the Islamic Law philosophy of the khuntsa marriage and how its application in Indonesia as well? This research answers the problem with normative, sociological and psychological approach. The data is collected by reading the relevant literatures and as the addition is by interviewing. The research concludes that generally those transgenders want to legally get married as the syariat however the Syara hints to forbid and even condemn the relation or the marriage of the same sex. The marriage of khuntsa must be regulated legally through the state legislation to validate the marriage in accordance with Islamic Syariat and marriage law in Indonesia. The application of khuntsa marriage law in Indonesia is very possible, because the Islamic law has became the sub system of constitution